Learning from the Past, Shaping the Future: 50 Years of Official Languages in Canada - Théberge, Raymond (Minorités linguistiques et société / Linguistic Minorities and Society, 2021)
Since the adoption of the Official Languages Act 50 years ago, Canada and the rest of the world have changed a lot. As we look back at the past half-century and imagine the next, it is important to take stock of both the successes obtained and the challenges that were faced since the Act came into effect.The year 1969 was pivotal in our history. On the one hand, the Act was born out of a national unity crisis between Canada’s English- and French-speaking communities. On the other hand, it belonged to a broader movement which was seeking to recognize Canadians’ rights and to pursue the democratization of our society. It is in recognizing that the Act contributed to national cohesion, to the advancement of official languages and the vitality of the communities that speak them across the country that our successes and challenges need to be evaluated.